Формування духовного світу студентства як важливе завдання вищої школи - Грень, Лариса Миколаївна; Чадаєва, К. Ю. (Донецький національний технічний університет, 2017)
У статті розкрита роль вищого навчального закладу і педагогів у формуванні духовного світу студентства. Визначено поняття "культура", "духовність", "внутрішній світ особистості". Наведено практичні приклади з реалізації прищеплення молоді загальнолюдських цінностей, самореалізації її творчого потенціалу, реалізації духовних потреб в освітньо-виховному процесі кафедри (на прикладі тематичних вечорів "Колокольный звон пасхальный", роботи літературно-музичної студії; занять з релігієзнавства, етики та естетики).

The article discloses the role of a higher education establishment and pedagogues in forming the students’ spiritual world. The notions of culture, spirituality, personality’s inner world have been defined. There are provided practical examples on realization of inculcation of universal values to young people, self-realization of their creative potential, realization of spiritual needs within the training-and-education process at a department (on the example of theme parties "The Easter Peal", the work of literature-and-music club, classes on religion study, ethics and aesthetics).
Forming the students’ spiritual world as an important task of higher school
Keywords: культура; духовність; ціннісні орієнтації; духовні цінності; світоглядне поле; особистість; culture; spirituality; value orientations; spiritual values; world outlook; inner world; personality